Knee joint stress analysis in standing - Oshkour, A.A.; Abu Osman, Noor Azuan; Davoodi, M.M.; Bayat, M.; Yau, Y.H.; Wan Abas, Wan Abu Bakar (2011)
Assessment of the stress distribution in the tibiofemoral joint during standing on both legs was the aim of the present work. The finite element method was employed to perform the current study. A compressive load of half of body weight (250N) was applied to the femur head. The cartilages perfectly attached to femur and tibia; and while the femur and menisci were allowed vertical motion, the tibia was fixed at its end. The tibiofemoral joint components were considered linear elastic material. Computed tomography images were used to create subject-specific three-dimensional models of tibiofemoral joints in the commercial finite element software package ABAQUS v6.7. Mechanical responses, such as contact pressures and compressive stresses of the joint, were measured. It was found during the standing the lateral side of tibiofemoral joint carry out more stress rather than medial part. Moreover, the contact area of the lateral side is larger than the medial side.